The Future of Complementarity: Disentangling Causes from Consequences - Barry, Kathryn E.; Mommer, Liesje; van Ruijven, Jasper; Wirth, Christian; Wright, Alexandra J.; Bai, Yongfei; Connolly, John; De Deyn, Gerlinde B.; de Kroon, Hans; Isbell, Forest; Milcu, Alexandru; Roscher, Christiane; et al. (Trends in ecology & evolution (Amsterdam), 2019)
Evidence suggests that biodiversity supports ecosystem functioning. Yet, the mechanisms driving this relationship remain unclear. Complementarity is one common explanation for these positive biodiversity–ecosystem functioning relationships. Yet, complementarity is often indirectly quantified as overperformance in mixture relative to monoculture (e.g., ‘complementarity effect’). This overperformance is then attributed to the intuitive idea of complementarity or, more specifically, to species resource partitioning. Locally, however, several unassociated causes may drive this overperformance. Here, we differentiate complementarity into three types of species differences that may cause enhanced ecosystem functioning in more diverse ecosystems: (i) resource partitioning, (ii) abiotic facilitation, and (iii) biotic feedbacks. We argue that disentangling these three causes is crucial for predicting the response of ecosystems to future biodiversity loss. Complementarity is currently used as both a cause for enhanced ecosystem functioning and a consequence of some community process. Using complementarity as a cause and a consequence makes it difficult to disentangle individual causes such as resource partitioning, abiotic facilitation, and biotic feedbacks. There is strong evidence that resource partitioning, abiotic facilitation, and biotic feedbacks occur in grassland systems but there is little evidence that explicitly ties them to the consequence of enhanced ecosystem functioning. Interactions between resource partitioning, abiotic facilitation, and biotic feedbacks may make the biodiversity–ecosystem functioning relationship stronger. Ecological gradients such as stress, enemies, and resources may allow us to disentangle the contributions of resource partitioning, abiotic facilitation, and biotic feedbacks to enhanced ecosystem functioning.